Synthesis and Solid-State Structure of (4-Hydroxy-3,5-diiodophenyl)phosphine Oxides. Dimeric Motifs with the Assistance of O-H···O=P Hydrogen Bonds - A. Bewick, Nicholas; Arendt, Agata; Li, Yan; Szafert, Sawomir; Lis, Tadeusz; A. Wheeler, Kraig; Young, Jonathon; Dembinski, Roman (Current Organic Chemistry, 2015)
(4-Hydroxy-3,5-diiodophenyl)diphenylphosphine oxide, bis(4-hydroxy-3,5-diiodophenyl)(phenyl) phosphine oxide, and tris(4-hydroxy-3,5-diiodophenyl)phosphine oxide were obtained via iodination reactions of corresponding mono-, bis-, and tris(4-hydroxyphenyl)phosphine oxides. Single-crystal X-ray diffraction studies showed each homologue forms O-H···O=P and π-stacking interactions with neighboring molecules to give inversion related dimeric motifs.
Keywords: hydrogen bonding